Pengalaman Ibu Dalam Memberi Makan Pada Anak Cerebral Palsy - Nyoman Sri Wahyuni; Eka Wahyuningrum; Andri Kenti Gayatina (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Background: Cerebral Palsy is a neuromotor disorder that affects the development of movement, muscle tone and body posture. The prevalence in Indonesia is 1-5 cases per 1000 children diagnosed with CP. This is caused by abnormalities in the developing part of the brain. CP children also experience Oropharyngeal dysphagia which can be characterized by problems in one or all phases of swallowing and chewing food. The aim of this research is to determine mothers' experiences in feeding children with CP. Objective: To find out mothers' experiences in feeding children with Cerebral Palsy. Method: This research is qualitative research with a phenomenological study approach. This research was carried out at YPAC (Foundation for Disabled Children) Semarang. Participants were 3 mothers selected using a purposive sampling technique who had moderate and severe CP children. Data were collected by conducting in-depth interviews using interview guidelines. The results of the interviews were transcribed and analyzed using the Colaizzi method. Results: The characteristics of the participants were 40 years - 46 years and the child with CP was a boy aged 14 years and 2 children with CP were girls aged 14 and 10 years. The study yielded three theree themes: 1) the way mothers process and serve soft and then rough food. 2) The mother's feeling of fear that the child will start eating later than the average age in general. 3) Mother regulates child's food portions. Conclusions: The mother's experience in feeding children with cerebral palsy is very important so that the mother knows how to process and serve food, control the mother's feelings of fear and regulate the child's portions.